Histological organization and microarchitecture of various cells lining the olfactory epithelium of Rita rita (Hamilton, 1822) (Siluriformes: Bagridae) - Kumar Ghosh, Saroj; Chakrabarti, Padmanabha (Biological Letters, 2013)
Rita rita is a carnivorous, bottom dwelling catfish inhabits in muddy dirty water and depends on olfactory sensation for procurement of food. The structural organization and function ofvarious cells lining its olfactory epithelium have been investigated by light and scanning electron microscopy. The elongated olfactory organ consists of 64-68 primary lamellae arising from a narrow median raphe. Sensory as well as non-sensory regions are distinctly oriented on each olfactory lamella. The sensory epithelium occupies the apical tongue-shaped area and basal part of the olfactory lamellae, whereas the middle part is covered with non-sensory epithelium. The sensory epithelium is composed of 2 types of dendrites of receptor cells (either ciliated or microvillous), labyrinth cells, and a large number of flagellated supporting cells. The non-sensory epithelium is made up of stratified epithelial cells having a different pattern of microridges and mucous cells. Variations in the cellular orientation of the various cells on the olfactory epithelium have been correlated with the functional views of the fish concerned.